Pulmonary Alveolar Microlithiasis(PAM) - Sarkar, Devendra Nath; Hossain, Md Ismail; Haque, Md Mahmudul; Zahin, AKM; Miah, Md Shahin; Ohab, MA; Hossain, Altaf; Saha, Beauty (Medicine Today, 2016)
PAM is a rare parenchymal Lung disease. Very few case report are available about PAM in Bangladesh. It is diagnosed incidentally during chest radiograph. It is a autosomal recessive disease and is associated with sporadic or familial mutation of SLC 34A2 gene. Many patients are asymptomatic and have either normal or restrictive pulmonary function. Some patients remain static and others progress into pulmonary dysfunction, respiratory failure and corpulmonale. The disease is usually discovered up to 40 years and there is no definitive treatment of this disease. Chest radiograph, HRCT used lung biopsy (transbronchial or open) are the main investigations. This patient come with chest pain and dyspnoea on exertion and nonproductive cough and diagnosed as PAM incidentally during chest radiograph. On the basis of clinical features and laboratory finding, we diagnosed him a case of PAM a very rare condition. As there is no definitive treatment, we treat himsymptomatically. Medicine Today 2015 Vol.27(2): 40-43